Projecting Potential Impact of European Union Deforestation Regulation on Indonesian Palm Oil Industry - Damanhuri, Achmad (International Journal of Science and Society, 2023)
As a commitment to realizing the Green Deal which aims to reduce greenhouse gas emissions, the European Union has issued new regulations, namely the European Union Deforestation Regulation (EUDR) which focuses on eradicating products related to deforestation and forest degradation. Several provisions are implemented ranging from due diligence requirements to state assessments based on a three-level system. Based on the international trade conflict that occurred previously between the European Union and Indonesia regarding palm oil commodities, the author uses a qualitative approach to analyze tendencies in the EUDR as a continuation of the European Union's new protectionism against Indonesian palm oil commodities through administrative barriers. Several potential impacts are also visible, ranging from disputes at the WTO to losses in the Indonesian economy and development.